2014
DOI: 10.1123/rsj.2014-0039
|View full text |Cite
|
Sign up to set email alerts
|

Intramural Sport Marketing: An Examination of Effectiveness, Participant Motives, and Demographic Differences

Abstract: Intramural sports exist as a relevant entity in the recruitment and retention of college students (Byl, 2002). The popularity of intramural sport has caused university recreational departments to increase intramural opportunities, thus increasing the need for more targeted marketing efforts. However, marketing strategies for intramural sport are not as refined, funded, or as thoroughly researched as strategies found within intercollegiate and professional sports (Schneider, Stier, Kampf, Wilding, & Haines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Regular PA has been unanimously considered the cheapest instrument of public health, and it is estimated that if physical inactivity reached (only) 50% of the Portuguese population, the costs would be around 900 million euros [4]. Additionally, the practice of regular PA is recognized as having benefits for quality of life, health, and wellbeing fairly described for people of all age groups, namely the improvement of brain health, weight management, disease reduction, bones and muscles strengthening, and the ability improvement to do everyday activities [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Regular PA has been unanimously considered the cheapest instrument of public health, and it is estimated that if physical inactivity reached (only) 50% of the Portuguese population, the costs would be around 900 million euros [4]. Additionally, the practice of regular PA is recognized as having benefits for quality of life, health, and wellbeing fairly described for people of all age groups, namely the improvement of brain health, weight management, disease reduction, bones and muscles strengthening, and the ability improvement to do everyday activities [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Popp and McEvoy (2014) found university athletic department so far unable to demonstrate the financial impact of social media on their bottom line. Studies by Ciuffo et al (2014), and Abeza and O'Reilly (2014) demonstrated that Twitter is less effective in sports marketing efforts than other forms of engagement, whereas Watkins (2014) found Twitter had a positive impact on brand equity for NBA fans. Notably, there do not appear to be studies that ascribe financial value in dollars to Twitter hashtag use.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that demonstrate the true bottom line impact of social media for sport organisations are somewhat limited. A study of the marketing of intramural sports found Facebook and Twitter to be far less effective at encouraging participants than traditional handouts (Ciuffo et al, 2014). Watkins (2014) found that social media, Twitter more than Facebook, had a positive impact on brand equity creation for fans of National Basketball Association teams.…”
Section: Twitter Hashtagsmentioning
confidence: 99%
“…This could be a greater issue for universities where there is a more diverse student population demographic, with multi-site campuses and more off-site student programs than the case here. The lack of student awareness about sport was also discussed by Ciuffo (2014) who examined the effectiveness of intramural sport marketing. The top three most effective marketing techniques were promotional items (such as free tshirts), mass e-mail and word of mouth and the three least effective marketing techniques in descending order were TV monitor, Facebook and Twitter.…”
Section: Bespoke Communicationsmentioning
confidence: 99%